THE ROLE OF THE WOMEN'S EMPOWERMENT AND CHILD PROTECTION OFFICE OF HULU SUNGAI UTARA REGENCY IN HANDLING DOMESTIC VIOLENCE AGAINST WOMEN - Nor Ainah; Syahrusiani Syahrusiani; Normaliyani Kartika Kartika (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
Several issues were identified in carrying out the functions of Women’s Empowerment and Child Protection Agency (DPPPA) of Hulu Sungai Utara Regency in handling domestic violence against women, including inadequate staff capacity in implementing programs to protect against violence against women, inadequate outreach, and limited facilities. This study used a qualitative approach with a descriptive qualitative approach. Data collection techniques included interviews, observation, and direct documentation in the field, with a sample size of 13 participants. Purposive sampling was used for sampling. After data collection, The analysis was conducted through data condensation, data display, and conclusion formulation. Data credibility was further tested, including extended participation, observational diligence, triangulation, peer review, reference adequacy, negative case review, and member checking. The results of this study, which examined the role of the DP3A of Hulu Sungai Utara Regency in handling domestic violence against women, were less than satisfactory.  Indicators that align with Sodang P. Siagian's theory include the level of legitimacy, implementation of innovation, social awareness, and responsibility. Indicators that do not align with Sodang P. Siagian's theory include selective ability, socialization, knowledge, facilities, human resources, and activities. Furthermore, there are supporting factors, such as the availability of counseling rooms, and inhibiting factors, such as the lack of budget, training, and guidance on handling and reporting domestic violence. Suggestions for the Head of the DP3A and staff include optimizing the budget, expanding outreach to villages, improving staff capacity through training and clear task allocation, adding human resources as needed, strengthening victim support, and strengthening family counseling services to prevent domestic violence. Victims and the community are encouraged to report cases of domestic violence to the DP3A immediately if they experience or witness them for protection and faster recovery.